BMP Signaling in Regulating Mesenchymal Stem Cells in Incisor Homeostasis. (July 2019) - Shi, C.; Yuan, Y.; Guo, Y.; Jing, J.; Ho, T.V.; Han, X.; Li, J.; Feng, J.; Chai, Y.
Bone morphogenetic protein (BMP) signaling performs multiple essential functions during craniofacial development. In this study, we used the adult mouse incisor as a model to uncover how BMP signaling maintains tissue homeostasis and regulates mesenchymal stem cell (MSC) fate by mediating WNT and FGF signaling. We observed a severe defect in the proximal region of the adult mouse incisor after loss of BMP signaling in the Gli1+ cell lineage, indicating that BMP signaling is required for cell proliferation and odontoblast differentiation. Our study demonstrates that BMP signaling serves as a key regulator that antagonizes WNT and FGF signaling to regulate MSC lineage commitment. In addition, BMP signaling in the Gli1+ cell lineage is also required for the maintenance of quiescent MSCs, suggesting that BMP signaling not only is important for odontoblast differentiation but also plays a crucial role in providing feedback to the MSC population. This study highlights multiple important roles of BMP signaling in regulating tissue homeostasis.